2010
DOI: 10.1038/ejcn.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

The effect of folinic acid supplementation on homocysteine concentrations in newborns

Abstract: Objective: The incidence of cerebrovascular accidents (CVA) occurring perinatally is relatively high and aspects of the multifactorial pathophysiology remain unclear. Elevated homocysteine concentrations have been shown to be associated with an increased risk for CVA in children and even in newborns. We studied the possible homocysteine lowering effect of folinic acid in newborns. Method: We included 37 newborns in our prospective randomized folinic acid (given as 5-formyltetrahydrofolate) intervention study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Also, studies in adults showed that folate supplementation reduced homocysteine levels in those with the TT genotype more than those with CC or TC genotype . However, in newborns, homocysteine levels were not affected by an increased folate, suggesting that homocysteine metabolism and response to folate is different in newborns, as compared with adults . In addition, we found that the effect of MTHFR C677T on folate metabolism is also different in newborns.…”
Section: Discussionmentioning
confidence: 48%
“…Also, studies in adults showed that folate supplementation reduced homocysteine levels in those with the TT genotype more than those with CC or TC genotype . However, in newborns, homocysteine levels were not affected by an increased folate, suggesting that homocysteine metabolism and response to folate is different in newborns, as compared with adults . In addition, we found that the effect of MTHFR C677T on folate metabolism is also different in newborns.…”
Section: Discussionmentioning
confidence: 48%
“…This represents the 97.5 percentile in 4 months old infants given a single intramuscular dose of 400 μg hydroxocobalamin at 6 weeks, rendering them to be cobalamin optimized (Bjørke-Monsen et al, 2008 ). In addition, administration of folinic acid in newborns did not reduce tHcy (Hogeveen et al, 2010 ). In older children and adults, tHcy is mainly a folate marker, while MMA is considered a good marker for cobalamin status (Bjørke Monsen and Ueland, 2003 ; Monsen et al, 2003 ).…”
Section: Vitamin B 12 Deficiency In Infantsmentioning
confidence: 99%
“…In addition, the recommended dose greatly exceeded the normal “folates” requirement of 500 to 800 µG per day in adults. FLA does not decrease plasma homocysteine levels in newborns who are at risk of ischemic and hemorrhagic stroke due to elevated Hcy [ 27 ]. FLA is rarely used in pathologies of reproduction/embryogenesis; however, its positive effect on counteracting the well-known deleterious effects of valproic acid on embryogenesis is controversial.…”
Section: Folate Malabsorptionmentioning
confidence: 99%